Atlas of microstructures of constructional materials: study aid - Egorov Yu. P. Yuri Petrovich; Strelkova I. L. Irina Leonidovna; Khvorova I. A. Irina Alexandrovna; Baginski A. G. Andrey Gennadievich (Tomsk, TPU Publishing House, 2019)
Title screen